Outdoor and indoor ozone level – A potential impact on human health - Valuntaitė, Vaida; Girgždienė, Raselė (Vojnosanitetski pregled, 2015)
Background/Aim. Air pollution outside and inside is still one of the most sensitive issues. The aim of this study was to assess the ozone level in ambient air and working premises in terms of its possible influence on human health. Methods. The study was based on the results obtained in Lithuanian conditions. Continuous ozone measurement data from the rural monitoring station in Preila over the period 1995–2011 were analyzed. More than 180,000 hourly values were examined according to the requirements in the Directive 2008/50/EC. The World Health Organization (WHO) and European Union indicators the Sum of Ozone Means Over 35 ppb (SOMO 35), the maximum daily 8-hour mean concentration of ozone higher than 100 and 120 μg/m3 were estimated. Indoor ozone concentrations in copying and welding rooms were evaluated. The ozone concentration was measured with the ozone analyzer O341M. Results. The frequency distribution of ozone hourly concentrations at the Preila station showed that less than 1% of the data were higher than 120 μg/m3 and 6% of them higher than 100 μg/m3, that could have the adverse effect on human health, during 1995–2011. The investigations made in working premises showed that near a copying machine the ozone concentration can reach 330 μg/m3, however in the room, i.e. 0.5 m from the machine, the average ozone concentration during automatic copying was 165 μg/m³ and during manual copying it was 50 μg/m³. Measurements in a welding room showed that the ozone concentration was in the range of 380–1,850 μg/m3 at the distance of 25 cm from the electrode and at the distance of 1 m from the source the ozone concentration decreased 2.5 times. Conclusion. The danger of the ambient ozone level to human health practically was not observed in Lithuanian conditions. However, almost 6% of the data exceed the new WHO guideline of 100 μg/m3 during the measurement time. Indoor ozone during welding reached a higher level than during copying that can cause human health problems.
Keywords: ozone; air pollution; indoor; welding; health; risk assessment